(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Ageing is a universal and socially constructed phenomenon. Old age is a natural stage phenomenon in the life of every human being. Theoretically, it precedes spontaneously right from a person’s moment of birth. Ageing comes to all organisms as a process of regular change that is invariably accompanied with clear and manifest decline in psychological competency. In India, people who have attained 60 years and above are defined as elderly. It is more a social construct rather than a biological stage. The process of ageing is a very individualistic phenomenon. But throughout the world, large numbers of older persons face challenges such as discrimination, poverty and Abuse that severely restrict their human right and their contribution to society. Human Rights are the basic rights which fundamentally and inherently belong to each individual. Thus, Human Right is fundamental rights which human being possesses by fact being human. According to United Nation’s Universal Declaration of Human Rights in 1948, include cultural, economic and political rights, such as right to life, liberty, education and equality and right of association, belief, free speech, information, religion movement and nationality. This paper try to analyse / examine the available laws, policies and protection of the human rights of old age person in Assam.